Soil microbiology, ecology, and biochemistry - Paul, Eldor Alvin; Paul, Eldor Alvin (Academic Press, 2007)
Now in its third edition, this classic textbook includes basic concepts and applications in agriculture, forestry, environmental science, and a new section entirely devoted to ecology. This revised and updated edition guides students through biochemical and microbial processes in soils and introduces them to microbial processes in water and sediments. Soil Microbiology, Ecology, and Biochemistry serves as an invaluable resource for students in biogeochemistry, soil microbiology, soil ecology, sustainable agriculture, and environmental amelioration. NEW TO THIS EDITION: * New section on Ecology integrated with biochemistry and microbiology * Sections on exciting new methodology such as tracers, molecular analysis and computers that will allow great advances in this field * Six new chapters: bioremediation, soil molecular biology, biodiversity, global climate change, basic physiology and ecological interpretations * Expanded with contributions from leading soil microbiologists and agronomists on both fundamental and applied aspects of the science * Full-color figures * Includes a website with figures for classroom presentation use.